Results of cherry rootstock evaluations in Hungary - Gyeviki, M.; Bujdosó, G.; Hrotkó, K. (International Journal of Horticultural Science, 2008)
The paper gives a review on the results of the latest rootstock evaluation projects in Hungary. Several cherry rootstock evaluation projects were carried out in Hungary during the last two decades. The evaluated rootstocks are partly mahalebs selected in Hungary, but more or less all the most important new rootstocks from different countries are involved. The aim of these evaluation projects was to find appropriate rootstocks in a wide range of vigour for our climate and soil conditions. The conclusion of the last 20 years of research in Hungary proved just the opposite of believes, that high density orchard can only be planted with dwarfing rootstocks. Before choosing the right rootstock the most important is to consider adaptability, precocity and productivity. Dwarfing and semi-dwarfing rootstocks showed proper results only with irrigation or very good site conditions. These rootstocks are very precocious, but branches form easily blindwood. This must be corrected by severe pruning in the first years. The relatively small leaf surface area can also be disadvantageous, but it can be controlled by pruning, fruit-thinning, irrigation and fertilization. After studying different rootstocks semi-vigorous rootstocks seem to be the most adequate for different site conditions in Hungary. Fast initial growing and competent precocity are their favourable characters. From the vigorous group of clonal mahalebs or seedlings are highly recommended first of all for poor site condition (sandy, lime soils with high pH). They turn to bearing early and easy to find them in the Hungarian nurseries. But on vigorous rootstocks trees might need stronger summer pruning.